1980
DOI: 10.1038/bjc.1980.32
|View full text |Cite
|
Sign up to set email alerts
|

Antigens of gastric and intestinal mucous cells in human colonic tumours

Abstract: Summary.-Using immunofluorescence methods, 3 antisera respectively stain 3 groups of mucous cells of the human gastrointestinal tract, showing specific antigens for each group of cells.The antigens of the first group, the MI antigens, were principally associated with columnar cells of the gastric epithelium, the M2 antigens with mucous cells of gastric and Brunner's glands, and the M3 antigen with the goblet cells of the intestinal mucosa.The gastric M antigens normally detectable in stomach and duodenum (but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 11 publications
2
55
0
1
Order By: Relevance
“…Despite the differences between patterns of mucin heterogeneity observed with anti-HCM MAbs and other methods within the colonic mucosa, the increasing cross-reactivity ofanti-HCM MAbs at progressively more distal sites of the gastrointestinal tract is comparable to the results of earlier studies (29,34). The present studies confirm the impression that some structural features are common to all gastrointestinal tract mucin, while other components of mucin may represent organ specific determinants.…”
Section: Discussionsupporting
confidence: 80%
“…Despite the differences between patterns of mucin heterogeneity observed with anti-HCM MAbs and other methods within the colonic mucosa, the increasing cross-reactivity ofanti-HCM MAbs at progressively more distal sites of the gastrointestinal tract is comparable to the results of earlier studies (29,34). The present studies confirm the impression that some structural features are common to all gastrointestinal tract mucin, while other components of mucin may represent organ specific determinants.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, several earlier studies have utilized probes directed to circumscribed nonreducing terminal structures to explore colonic mucin heterogeneity. These probes have included lectins that recognize terminal monosaccharides or disaccharides (18,22,33,34), histochemical stains that bind peripheral charged residues (1 1, 30, 35, 36) or conventional antisera directed at limited peripheral carbohydrate determinants (17,37,38). The present results suggest that relatively nonspecific tools may both underestimate heterogeneity and overestimate structural homologies.…”
Section: Discussionmentioning
confidence: 79%
“…[15][16][17][18] HGM is a specific marker for core protein of gastric foveolar cells. 19,20) The correlations between positivity to these antibodies and clinicopathologic features suggested that cell differentiation is inversely associated with tumor growth and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We selected three immunohistochemical markers for cell differentiation: MUC2 for intestinal goblet cells, [12][13][14] CD10 for small intestinal brush border [15][16][17][18] and human gastric mucin (HGM) for gastric differentiation. 19,20) A representative section from each tumor was processed for immunohistochemical staining with monoclonal antibodies against MUC2 (Novocastra, Newcastle-upon-Tyne, UK, diluted 1:200), CD10 (Novocastra, diluted 1:200) and HGM (45M1, Novocastra, diluted 1:50). Four-micron-thick sections were cut, deparaffinized in xylene and dehydrated in an ethanol series.…”
Section: Methodsmentioning
confidence: 99%